PENGARUH PRODUK, HARGA, TEMPAT, PROMOSI DAN KEBUTUHAN MENCARI KERAGAMAN TERHADAP PERPINDAHAN MEREK SAFE CARE KE MEREK LAIN - Amalia, Putri (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2018)
Abstract: The presence of competitors and the number of brands that increase in the category ofrefreshing oil aromatherapy makes the competition increasingly tight and provides opportunities forcustomers to be able to make switching of brand in accordance with the wishes and expectation. Thisstudy aims to determine the effect of products, prices, places, promotions and variety seekingpartially and simultaneously on brand switching of Safe Care to other brands in DKI Jakarta. Datawas conducted by survey with questionnaire as an instrument, while the variables in the researchwere valued using Likert Scale. The samples were taken with a non-probability sampling design withpurposive sampling. The number of samples used is 200 respondents. The SEM (Structural EquationModelling) method was used as a data analysis technique. The result of this research shows that theproduct have significant effect on the brand switching with t-value 2.00, price have significant effecton the brand switching with t-value 2.79, place have significant effect on the brand switching with tvalue2.33, promotion have significant effect on the brand switching with t-value 2.05, and thevariety seeking have significant effect on the brand switching with t-value 5.90. On the SEM model,product, price, place, promotion and variety seeking simultaneously have significant effect on brandswitching indicates a statistical value that meets the Goodness of Fit criteria. Based on the result ofthe research, the conclusion that can be taken is partially and simultaneously the variable of product,price, place, promotion and variety seeking have positive and significant effect on the brandswitching of Safe care to other brands in DKI Jakarta.